Active Collision Avoidance for Human – KUKA Robot Collaboration driven by Ultrasonic Sensor HC-SR04 - Ahmad Al-Husna, Sabrina Ilmuna (IRC, 2018)

(untitled)
Human robot collaboration was made possible with the anti-collision mechanism that exist today with the help of distance detection devices such as the ultrasonic sensor. The versatile and cost-effective sensor has good accuracy, but its readings may be influenced by other factors. In this Final Year Project, it aims (1) to analyse the accuracy of ultrasonic sensor on the KUKA KR 3 Robot, (2) to identify the causes of inaccuracy of ultrasonic sensor on the KUKA KR 3 Robot, (3) to recommend improvements to accuracy of ultrasonic sensor and (4) to display a safety message to notify the user that the obstacle is too close. The method that is applied is to utilise the ultrasonic sensor HC-SR04 connected to Arduino UNO board which is attached onto the gripper of the robot will detect the distance of the obstacle and display a warning message. It was discussed that the elements that influence the readings of the ultrasonic sensor were the temperature and humidity of surrounding, the range of the ultrasonic sensor and the angular deviation of the surface. Hence, the accuracy of the ultrasonic sensor was analysed as the error value was higher as the obstacle was closer to the sensor by the range of 7.9% - 20.75 % of error value. A safety message was displayed as “Please press STOP button” when the obstacle was less than 10.0 cm away from the sensor. It was also recommended that the ultrasonic sensor should be “warmed up” before being used in the experiment, the surrounding temperature and humidity of the experiment location should be changed to be room temperature of 27C, the range of the of ultrasonic sensor should be considered when placing the sensor on the robot and the obstacle should be made of reflective material that has less porosity like metal or wood.